GSH-responsive sequential mitochondria-targeting nanoagents for photothermal-enhanced chemodynamic therapy. (July 2022) - He, Huaming; Zhao, Fang; Zhong, Wukun; Yang, Yuling; Lin, Yuhong; Ding, Yihang; Yang, Jiajia; Lu, Chunhua; Tu, Xiankun
Graphical abstract: Highlights: Glutathione-responsive nanoagents which contains of CuFeS2 nanoparticles and two targeting peptides was designed for photothermal-enhanced chemodynamic therapy. The nanoagents could progressively and precisely target to mitochondria of tumor cell via the mitochondrial-targeting peptide and integrin-targeting peptide. The Fenton reaction of the nanoagents was enhanced due to the excellent photothermal effect of CuFeS2 under NIR laser irradiation. The therapeutic nanoagents could effectively damage the mitochondrial function and further induce the apoptosis of tumor cells. Abstract: Mitochondria-targeting nanoparticles have proven to be promising platforms for cancer therapy. However, precise mitochondria targeting in the complex tumor environment is still challenging and requires more ingenious design. Herein, we developed the glutathione (GSH)-responsive nanoagents to target mitochondria in tumor cells precisely for photothermal-enhanced chemodynamic therapy (CDT). The nanoagents were designed by preparing the cubic shape of CuFeS2 nanoparticles that sequentially modified with mitochondrial-targeting peptide (KLAK) and integrin-targeting peptide (RGD), which KLAK and RGD were covalently conjugated via a disulfide bond. After being endocytosed into integrin-overexpressed tumor cells, disulfide bond was broken and RGD was separated from the nanoagents in the presence of overexpressed GSH. Then, the exposure of KLAK on the surface further aid the rustling nanoagents to target mitochondria. Under NIR laser irradiation, the surrounding temperature of the nanoagents would rise due to their excellent photothermal effect, resulting in the improvement of the Fenton reaction from the CuFeS2. It was well demonstrated that this photothermal-enhanced chemodynamic therapy nanoplatform could effectively damage the mitochondrial function and further induce the apoptosis of tumor cells. As a therapeutic platform with both tumor/mitochondria-targeting and PTT-enhanced CDT, our study has provided a new path in the field of cancer therapy.